PERCEPTION AND SOCIODEMOGRAPHIC PROFILE OF CONSUMERS IN THE ONLINE ENVIRONMENT - Tomašević, Dragana; Kocić, Milan; Tomašević, Stevan M (Economic Outlook, 2023)
The aspiration and goal of any company operating in an online environment are to be successful, competitive, and profitable. Current trends in the development of internet trade must be followed to achieve these goals. Companies must continuously adjust their business to new trends that change from year to year. Given the growing importance of this type of purchase, it has become imperative to identify factors that influence consumer behavior in the online environment. Therefore, the main goal of this article is to analyze the behavior of online consumers when purchasing products and services from aspects of different consumer characteristics and their perception of risk and the benefits they have from this way of buying.
Keywords: consumer; perception; sociodemographic characteristics; online environment